Cervical-scapular muscles strength and severity of temporomandibular disorder in women with mechanical neck pain - Fernanda Pasinato; Juliana Bordin; Clarissa C. Santos-; Juliana Alves Souza; Eliane C. R. Corrêa
Abstract Introduction: Changes in cervical muscle function have been observed in patients with neck pain (NP) and TMD. However, the relationship between TMD severity and neck muscle strength in the presence/absence of NP is unknown. Objective: To determine the prevalence of TMD in women with and without mechanical NP and assess the cervical-scapular muscle strength and its association with TMD severity. Methods: Fifteen volunteers without neck pain (CG) and 14 women with mechanical neck pain (NPG) took part and were selected by the Neck Disability Index. The diagnosis and severity of TMD were determined by the Research Diagnostic Criteria for TMD and Temporomandibular Index (TI), respectively. The strength of the upper trapezius muscle, and cervical flexor and extensor muscles was measured by digital hand dynamometer. Results: 64.5% of women with NP and 33.3% without NP were diagnosed with TMD (p = 0.095). The NPG showed lower strength of the cervical flexor (p = 0.044) and extensor (p=0.006) muscles, and higher TI (p = 0.038) than in the CG. It was also verified moderate negative correlation between TI and the strength of dominant (p = 0.046, r = -0.547) and non-dominant (p = 0.007, r = -0.695) upper trapezius, and cervical flexors (p = 0.023, r = -0.606) in the NPG. Conclusion: There was no difference in the prevalence of TMD in women with and without NP. However, women with NP have lower cervical muscle strength - compared to those without NP - which was associated with greater severity of TMD. Thus, in women with NP associated with TMD, it is advisable to assess and address the severity of this dysfunction and identify the cervical-scapular muscles compromise.